Elemental compositions and anti-anemic property of Harungana madagascariensis stem bark - Ezekiel O. Iwalewa1, Nusrat O. Omisore1, Oluwatoyin M. Daniyan, Clement O. Adewunmi, Bamigboye J. Taiwo, Oluwatobi A. Fatokun and Isaac O. Oluborode (Bangladesh Pharmacological Society, 2009)
The concentrations of 15 elements and heavy metals in the stem bark of Harungana madagascariensis were determined using an energy-dispersive X-ray fluorescence (EDXRF) spectrometer. The anti-anemic activity was done using the changes in hematological parameters (PCV, RBC and Hb) influenced by phenylhydrazine HCL (80 mg/kg) and malaria parasites-induced anemia. Results show Cd, Ni, Mo, Cr and Br were in the range of 0.021-0.94 mg/g, while Pb, Zn, Fe, Cu and Hg were in the range of 1.50-7.24 mg/g. The elements with very high concentration were Ca, K, Sr, Mn and Cl and were in the range of 10.5-774.3 mg/g. Remarkable anti-anemic activity was obtained with PCV of 40-48%, RBC count of 81-155 x104 and Hb value of 57-66 g/dL after treatment; compared with 30% PCV, 67 x104 RBC count and 36.5 g/dL Hb value obtained for the untreated control animals. Our results suggest that H. madagascariensis stem bark extract constituents exhibit anti-anemic activity.